Josephson current mediated by ballistic topological states in Bi2Te2.3Se0.7 single nanocrystals - Vasily S. Stolyarov (Nature Portfolio, 2020)
Topological insulators in contact with a superconductor could house unusual physical states such as Majorana fermions. Here, the authors fabricate and report the  electron-transport characteristics of Josephson junctions built using a nanoscale topological insulator, finding evidence for ballistic transport in the surface states of the nanocrystals.